Spinning of hydroalcoholic chitosan solutions: Mechanical behavior and multiscale microstructure of resulting fibers. Issue 9 (8th October 2018) - Desorme, M.; Montembault, A.; Tamet, T.; Maleysson, P.; Bouet, T.; David, L.
ABSTRACT: The morphology and mechanical properties of chitosan fibers obtained by spinning of hydroalcoholic (1, 2propanediol/water) chitosan solutions of low DA and high molecular mass are reported. The impact of processing parameters on final fiber properties, such as fiber stretching at different steps of the spinning process, is investigated. A stretching ratio applied during the fiber coagulation appeared to have no significant effect on mechanical properties, whereas fiber drawing after the coagulation step, that is, during the washing step was a key parameter for the control of macromolecular orientation, fiber tenacity, and Young's modulus. The microstructure and morphology of the various as‐spun chitosan fibers were studied by means of wide‐angle and small‐angle X‐ray scattering and scanning electron microscopy. Microstructure impacts mechanical properties from the interplay of different deformation mechanisms acting at different length scales of the microstructure, namely the macromolecular orientation, the semicrystalline morphology, and the core–shell structure. The obtained monofilament fibers (45–70D) can be knitted. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47130. Abstract :